Sistem Informasi Penerimaan Siswa Baru Berbasis Android dengan Push Notifikasi di SMK PGRI 1 Palembang - Dopri; Ghazali, K. (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
SMK PGRI 1 Palembang annually holds PSB activities where currently prospective new students can register by coming directly to the information section, filling out the Google Forms form, or contacting the WA PSB officer. These three registration methods have several drawbacks such as additional expenses for ATK and transportation, as well as a limited registration time. In addition, officers must re-enter data from new prospective students with the existing desktop system because the database has not yet been integrated and new prospective students need to be contacted one by one if there are changes such as changes to the briefing schedule. This resulted in PSB activities at SMK PGRI 1 PALEMBANG being less efficient, tiring, and slow. The proposed solution to the problem is to create an Android-based PSB application with push notifications and integrated with the current MSYQL database. Push notifications allow direct notifications to be sent to certain parties if an event occurs such as a new registration or registration being responded to by the admin. This means that new registrations can be immediately recognized and responded to by the admin.